Challenges in management of refractory pain and sedation in infants - Oschman, Alexandra; Rao, Karishma (Frontiers in Pharmacology, 2024)
The survival of preterm infants continues to improve, along with an increase neonatal intensive care unit (NICU) management of chronic infants who are medically complex infants who have prolonged hospital stays, sometimes up until two years of age. Despite advances in neonatal and infant care, the management of pain and sedation in chronic NICU patients continues to be a challenge. Challenges such as development of appropriate pain, sedation, and withdrawal scales along with unfamiliarity of the NICU care team with pediatric disease states and pharmacotherapy complicate management of these patients. Opioid induced hyperalgesia (OIH) and delirium may play a large role in these refractory cases, yet are often not considered in the NICU population. Drug therapy interventions such as gabapentin, ketamine, risperidone, and others have limited data for safety and efficacy in this population. This article summarizes the available literature regarding the evidence for diagnosis and management of infants with refractory pain and sedation along with the challenges that clinicians face when managing these patients.